Political equality and the process of candidate selection: MPs' views in comparative perspective - Freire, A.; Lisi, M. (Representation, 2012)
There has been an increasing concern in contemporary democracies about political equality and descriptive representation. But to what extent do MPs consider legitimate the selection of candidates according to their social background? Drawing on the PARENEL project data, our results indicate that age and gender are the two most legitimate criteria from the MPs' normative view. Yet there are significant differences among countries and political parties. In particular, left-wing MPs are more prone to support the selection of prospective MPs based on principles of social equality, whereas Belgian MPs display higher levels of consensus towards descriptive type of recruitment.